Partner notification for sexually transmitted infections and perception of notified partners - Elani Graça Ferreira Cavalcante; Mahara Coelho Crisostomo Miranda; Ana Zaiz Flores Hormain Teixeira de Carvalho; Ivana Cristina Vieira de Lima; Marli Teresinha Gimeniz Galvão (SciELO, 2016)
Abstract OBJECTIVE Learn the perceptions of patients with sexually transmitted infections and sexual partners who are notified of the infection. METHOD A descriptive and qualitative study, based on the collective subject discourse technique, was conducted in four healthcare centers of reference in Fortaleza, Ceará, from March to July 2014. The sample comprised 21 subjects (11 index patients and 10 notified partners). RESULTS The index patients reported complicity, concern about the partner's health and revelation of diagnosis aiming to preserve the relationship. The partners showed antagonistic perceptions: tranquility-betrayal, fear of death, of incurability and the diagnosis, especially of HIV. The reasons for coming to a healthcare center were: fear of being sick, attenuation of guilt of infection transmission, need for diagnosis, early start of treatment. CONCLUSION Fear of losing trust, insecurities when dealing with a sexual infection and being responsible or co-responsible for the transmission were the predominant feelings. Various types of partner notification were reported (verbal, telephone, notification card), according to individual convenience. This study suggests the use of alternative methods of notification and an integrated system of notification.